Konstruksi Puasa Waqi'ah - Muhammad Anwar Idris (Jurnal Living Hadis, 2020)
Fasting is divided into at least two groups, namely required fasting and non-required fasting. The only fast that is required in Islam is fasting during Ramadan. In addition to fasting on Mondays and Thursdays, there is one type of fasting done at Pondok Pesantren an- Nur 1, Bululawang, Malang, East Java, which is interesting. Motivation, method of implementation, history, transmission- transformation of Waqi'ah fasting are special and far different from other non-required fasts. The interview, observation, documentation, and utilization of the living hadith approach used in this study, is able to uncover the fact that this fast is a "unique" fast that is only found in Pondok Pesantren an Nur and places the kiai of the pondok pesantren as an agent who has a major role in the formation of this Waqi'ah fasting tradition. This fast originates from the transformation and construction of the benefit of surah al-Waqiah. The fasting which is carried out for seven consecutive days needs to be done together with the dhikr and read the surah al-Waqiah. Waqi’ah fasting must obtain permission from the kiai (ijazah). As the hadith is used as the basis for the implementation of this fast, the purpose of the implementation of this fast is none other than to get great fortune.